3-D surface stereometry studies of sputtered TiN thin films obtained at different substrate temperatures - Stach, Sebastian; Sapota, Wiktoria; Ţălu, Ştefan; Ahmadpourian, Azin; Luna, Carlos; Ghobadi, Nader; Arman, Ali; Ganji, Mohsen (Journal of materials science. Materials in electronics, 2017)
Nanostructured glass-supported thin films of titanium nitride (TiN) were prepared by reactive magnetron sputtering at different substrate temperatures (from 25 to 400 °C). The surface topography of such films was examined by atomic force microscopy (AFM). The obtained 3-D AFM images was divided into motifs of significant peaks and pits using MountainsMap ® Premium software, which uses the watershed segmentation algorithm. In the motif analysis, parameters consistent with ISO 25178-2: 2012 and that characterize essential characteristics of the segmented motifs in terms of surface dimensions, volume, curvature, shape, structure, etc. were calculated, and the highest and lowest points of motifs were localized. This study allowed us to perform a quantitative correlation between synthetic conditions of TiN thin films and their 3-D micro-textured surface properties. Concretely, we found a non-monotonic dependence of the surface morphology properties of the thin films on the substrate temperature during the sample deposition, obtaining the most regular surface at a substrate temperature of 250 °C and the most irregular topography at the substrate temperature of 400 °C.